2015
DOI: 10.1016/j.nmd.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing and identification of genetic variants in sporadic inclusion body myositis

Abstract: Sporadic inclusion body myositis (sIBM) has clinical, pathologic and pathomechanistic overlap with some inherited muscle and neurodegenerative disorders. In this study, DNA from 79 patients with sIBM was collected and the sequencing of 38 genes associated with hereditary inclusion body myopathy (IBM), myofibrillar myopathy, Emery–Dreifuss muscular dystrophy, distal myopathy, amyotrophic lateral sclerosis and dementia along with C9orf72 hexanucleotide repeat analysis was performed. No C9orf72 repeat expansions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 44 publications
3
58
0
Order By: Relevance
“…We detected no TARDBP mutation associated with IBM, which is consistent with Qian Gang et al's study (Qian Gang et al, 2014) [9]. We did not detect pathogenic hexanucleotide expansion in C9ORF72, which is the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) with TDP-43 inclusions (Weihl et al, 2015) [18]. Other possible genes associated with the disease may be HNRNPA1 and HNRNPA2B1 [16].…”
Section: Discussionsupporting
confidence: 90%
“…We detected no TARDBP mutation associated with IBM, which is consistent with Qian Gang et al's study (Qian Gang et al, 2014) [9]. We did not detect pathogenic hexanucleotide expansion in C9ORF72, which is the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) with TDP-43 inclusions (Weihl et al, 2015) [18]. Other possible genes associated with the disease may be HNRNPA1 and HNRNPA2B1 [16].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we have found the missense p.I27V variant in a patient with a definitive diagnosis of lower MND with accompanying argyrophilic grains and mild AD-pathology, which may justify the clinical bvFTD syndrome as no classical FTLD pattern was observed. This mutation has been reported in a case with sporadic, isolated inclusion body myositis,23 a case with a progressive speech disturbance with no evidence of myopathy and a patient with a typical bvFTD 22. Thus, the VCP gene might have pleiotropic effects and a particular mutation in VCP can give rise to different phenotypes.…”
Section: Discussionmentioning
confidence: 94%
“…A recent Japanese study which screened for mutations in known hIBM and myofibrillar myopathy genes in a group of 21 patients with a diagnosis of inclusion body myositis did not find any mutations in VCP or GNE, but three patients had a mutation in MYHC2A which causes hIBM-3 (Cai et al, 2012). In another study of 79 IBM patients, pathogenic mutations in VCP were found in two patients who met the diagnostic criteria for IBM (Weihl et al, 2015). These findings emphasize the importance of defining stricter clinical and laboratory criteria for the diagnosis of sporadic inclusion body myositis and differentiation from hIBM.…”
Section: Brief Overview Of Pathogenesis and Genetic Susceptibility Famentioning
confidence: 99%